Impact of residual pulmonary obstruction on the long-term outcome of patients with pulmonary embolism. Issue 5 (25th May 2017) - Pesavento, Raffaele; Filippi, Lucia; Palla, Antonio; Visonà, Adriana; Bova, Carlo; Marzolo, Marco; Porro, Fernando; Villalta, Sabina; Ciammaichella, Maurizio; Bucherini, Eugenio; Nante, Giovanni; Battistelli, Sandra; et al.
The impact of residual pulmonary obstruction on the outcome of patients with pulmonary embolism is uncertain. We recruited 647 consecutive symptomatic patients with a first episode of pulmonary embolism, with or without concomitant deep venous thrombosis. They received conventional anticoagulation, were assessed for residual pulmonary obstruction through perfusion lung scanning after 6 months and then were followed up for up to 3 years. Recurrent venous thromboembolism and chronic thromboembolic pulmonary hypertension were assessed according to widely accepted criteria. Residual pulmonary obstruction was detected in 324 patients (50.1%, 95% CI 46.2–54.0%). Patients with residual pulmonary obstruction were more likely to be older and to have an unprovoked episode. After a 3-year follow-up, recurrent venous thromboembolism and/or chronic thromboembolic pulmonary hypertension developed in 34 out of the 324 patients (10.5%) with residual pulmonary obstruction and in 15 out of the 323 patients (4.6%) without residual pulmonary obstruction, leading to an adjusted hazard ratio of 2.26 (95% CI 1.23–4.16). Residual pulmonary obstruction, as detected with perfusion lung scanning at 6 months after a first episode of pulmonary embolism, is an independent predictor of recurrent venous thromboembolism and/or chronic thromboembolic pulmonary hypertension. Residual pulmonary obstruction after PE is an independent predictive factor of VTE recurrences and/or CTEPH http://ow.ly/XK49308SDTd